Tecendo um traçado entre autoformação docente e sentidos do trabalho - Lapa, Bárbara Castro (2017)
The research aimed to understand the senses of job in the Vocational and Technological Education teachers discourse at the Instituto Federal de Educação, Ciência e Tecnologia do Amazonas – IFAM as a basis for a self-formation proposal. The concepts of teacher training for Vocational and Technological Education, Senses of Teaching Job and Self-formation were specifically articulated as the research theoretical support. An investigative path, through life histories reported in interviews recorded and later transcribed, was designed to know the job senses of five IFAM teachers inserted in Vocational and Technological Education. Therefore the job senses of Vocational and Technological Education teachers were possible to become evident from the Discursive Textual Analysis (ATD) elements which allowed to understand them as a social responsibility, experiences and identity. This perception enabled the preparation, implementation and evaluation of a formative proposal, a Massive Open Online Course (MOOC), that aimed to develop a critical-reflective understanding in the participant regarding Vocational and Technological Education and in a specific way, (re) think the formative process itself from the life histories of teachers inserted in Vocational and Technological Education; to know the theoretical link between Self-formation, Senses of Teaching Job, Integral or Omnilateral Formation, Job as Educational Principle and Politecnia; and produce an e-portfolio composed by activities developed along the course. The MOOC, available on the IFAM online courses platform (http://mooc.ifam.edu.br:15000/), provided a self-formation process opportunity from what was understood about the job senses in the IFAM teachers speech as perceived in the Professional and Technological Education (ProfEPT) master's degree considerations, collaborators in the course evaluation based on the Professional and Technological Education and Self-formation.